Performance and Stability Comparison of Low-Cost Mixed Halide Perovskite Solar Cells: CH3NH3PbI3-xClx and CH3NH3PbI3-xSCNx - Nji Raden Poespawati; Junivan Sulistianto; Tomy Abuzairi; Retno Wigajatri Purnamaningsih (International Journal of Photoenergy)
Perovskite solar cell is categorized as a third-generation solar cell which is used for its high-performance and low-cost production. However, device stability is a major problem in the development of perovskite solar cells. Mixed halide perovskite is one of the subjects that have been proposed to improve perovskite solar cell stability. Research about solar cells using mixed halide perovskite is widely reported. However, complex configurations and fabrication using sophisticated equipment were usually used in those reported studies. In this work, the fabrication of solar cells using mixed halide perovskite CH3NH3PbI3-xClx and CH3NH3PbI3-xSCNx was conducted using a simple and low-cost structure. Solution-processed deposition fabrication method using spin coating was used to fabricate the devices. Optimization of the spin coating rate for each layer in the perovskite solar cells was performed to ensure that the devices exhibited decent performance. Stability measurement and analysis of the perovskite solar cells were conducted. Summarily, solar cells with mixed halide perovskite CH3NH3PbI3-xClx exhibit the highest performance with an efficiency of 2.92%. On the other hand, solar cell with mixed halide perovskite CH3NH3PbI3-xSCNx has the best stability which only drops its efficiency by 39% from its initial value after 13 days.